An evaluation of the disaster management plan of the selected libraries in Quezon City and recommendations towards the next five (5) years - Cruzata, Ivy S.; Apolinario, Rhea Rowena U.; Lagrama, Eimee Rhea C.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2015)
The study evaluated the existing disaster management plan of the six academic libraries in Quezon City based on National Disaster for Risk Reduction Management Council (NDRRMC) framework for disaster management. The six academic libraries in Quezon City are, Far Eastern University- Nicanor Reyes Memorial Foundation Library (FEU-NRMF), National College of Business Administration (NCBA), STI College - Fairview Campus (STI), AMA Computer University - Fairview Campus (AMACU), Our Lady of Fatima University - Fairview Campus (OLFU) Polytechnic University of the Philippines Commonwealth Campus (PUP).
The study focused on the strengths and weaknesses of the disaster management plans of the six academic libraries in the areas of : a. Earthquakes, Fire and Flood Prevention and Detection; b. Emergency supplies/disaster kits and Disaster Emergency Team.
The study also identified the factors that hinder the efficient implementation of their disaster management plan of the six academic libraries in Quezon City.
The study found out that the six academic libraries in Quezon City do not follow the framework created by The National Disaster Risk Reduction and Management Council (NDRRMC) for disaster management plan. Five out of six of these institutions only have initial planning for disaster and neglected the six remaining steps for the pre-disaster phase. All of these institutions do not have a plan in place for the Disaster and Post-Disaster phase. For the Strengths and Weaknesses of the disaster management plan of each libraries: five out of six institutions have a strong building that met the criteria for earthquake inspection and five out of six institutions do not have the equipment/gadgets if a fire or a flood strikes them.
Lastly, the study identified the factors why a separate disaster management plan was not implemented in their libraries. Survey results revealed that for all respondents budget is the main constraint, followed by the lack of support from the management and the lack of manpower. Another reason given was lack of long-term tenure of the employees. There is no continuity program which can be continued by the next person who will occupy the position.
The six selected academic libraries have no existing library disaster management plan in place. Thus, they are considered non-compliant because they do not follow a standard disaster management plan set by National Disaster for Risk Reduction Management Council (NDRRMC). The researcher believes that the lack of awareness is the main factor that hinders the implementation of the said plan in their library.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Quezon City; Emergency management -- Philippines -- Quezon City